Update in Hospital Medicine: Practical Lessons from the Literature. Issue 9 (27th February 2018) - Burger, Alfred; Miller, Chad; Sharpe, Bradley A.; Thompson, Rachel E.
Abstract : BACKGROUND: Hospital Medicine has a widening scope of practice. This article provides a summary of recent high‐impact publications for busy clinicians who provide care to hospitalized adults. METHODS: The authors reviewed articles published between March 2016 and March 2017 for the Update in Hospital Medicine presentations at the 2017 Society of Hospital Medicine and Society of General Internal Medicine annual meetings. Nine of the 20 articles presented were selected for this review based on the article quality and potential to influence practice. RESULTS: The key insights gained include: pulmonary embolism may be a more common cause of syncope and acute exacerbation of COPD than previously recognized; nonthoracic low‐tesla MRI is safe following a specific protocol for patients with cardiac devices implanted after 2001; routine inpatient blood cultures for fever are of a low yield with a false positive rate similar to the true positive rate; chronic opioid use after surgery occurs more frequently than in the general population; high‐sensitivity troponin and a negative ECG performed 3 hours after an episode of chest pain can rule out acute myocardial infarction; sitting at patients' bedsides enhances patients' perception of provider communication; 5 days of antibiotics for community‐acquired pneumonia is equivalent to longer courses; oral proton pump inhibitors (PPI) are as effective as IV PPIs after an esophagogastroduodenoscopy (EGD) for the treatment of bleeding peptic ulcers. CONCLUSIONS: Recent research provides insight into how we approach common medical problems in the care of hospitalized adults. These articles have the potential to change or confirm current practices.